Activated macrophages promote hepatitis C virus entry in a tumor necrosis factor‐dependent manner. Issue 4 (25th February 2014) - Fletcher, Nicola F.; Sutaria, Rupesh; Jo, Juandy; Barnes, Amy; Blahova, Miroslava; Meredith, Luke W.; Cosset, Francois‐Loic; Curbishley, Stuart M.; Adams, David H.; Bertoletti, Antonio; McKeating, Jane A.
<x xml:space="preserve">Abstract</x> Macrophages are critical components of the innate immune response in the liver. Chronic hepatitis C is associated with immune infiltration and the infected liver shows a significant increase in total macrophage numbers; however, their role in the viral life cycle is poorly understood. Activation of blood‐derived and intrahepatic macrophages with a panel of Toll‐like receptor agonists induce soluble mediators that promote hepatitis C virus (HCV) entry into polarized hepatoma cells. We identified tumor necrosis factor α (TNF‐α) as the major cytokine involved in this process. Importantly, this effect was not limited to HCV; TNF‐α increased the permissivity of hepatoma cells to infection by Lassa, measles and vesicular stomatitis pseudoviruses. TNF‐α induced a relocalization of tight junction protein occludin and increased the lateral diffusion speed of HCV receptor tetraspanin CD81 in polarized HepG2 cells, providing a mechanism for their increased permissivity to support HCV entry. High concentrations of HCV particles could stimulate macrophages to express TNF‐α, providing a direct mechanism for the virus to promote infection. Conclusion: This study shows a new role for TNF‐α to increase virus entry and highlights the potential for HCV to exploit existing innate immune responses in the liver to promote de novo infection events. (Hepatology 2014;59:1320‐1330)